(untitled) (Revista Apotheke, 2019)
This article intends to think about the processes of teacher- artist formation, taking as perspective the exploration concept. This concept was drawn from explorations in abandoned places and derived from an artistic project that became part of the research investments of the author. In this sense, the term designated for the artistic production also grew up with the theoretical questions. This possibility introduced another point of view about teacher formation in Visual Arts through the paths that compose the teacher-artist. These paths go beyond the formal learning fields and feed themselves with the diversity of actions carried out throughout the training processes.